RANCANGAN BANGUN KOMIK SEJARAH PERSIAPAN KEMERDEKAAN INDONESIA PADA MATA PELAJARAN IPS DI SD - Vera Ironita Christiani Sihombing; Eddy Noviana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Presentation of historical material in social studies learning in elementary schools, in general, still uses media in the form of textbooks. Not many media are available so learning activities become menotonous and unattractive. The presence of media is very important in the learning process. This study aims to determine the feasibility of comic-based learning media media on historical concepts in social studies in grade V elementary school. This research is a development research in 4 stages of implementation, namely research and information gathering, planning, developing the initial form of the product, and validating. The results of the evaluation of comic media are shown by an average score, namely material expert I at 88% with a very decent category, material expert II at 90.33% with a very decent category, media expert at 95% with a very decent category. Based on the results of expert tests, educators and limited trials, comic media in social studies subjects in elementary schools are in the very feasible category and can be used as learning media.